2021
DOI: 10.3389/fneur.2020.592888
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Research on SARS-CoV-2 Infection Causing Neurological Diseases and Its Infection Mechanism

Abstract: COVID-19 has spread rapidly worldwide since its outbreak and has now become a major public health problem. More and more evidence indicates that SARS-CoV-2 may not only affect the respiratory system but also cause great harm to the central nervous system. Therefore, it is extremely important to explore in-depth the impact of SARS-CoV-2 infection on the nervous system. In this paper, the possible mechanisms of SARS-CoV-2 invading the central nervous system during COVID-19, and the neurological complications cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Although the great majority of people infected with SARS-CoV-2 develop only mild or asymptomatic disease, COVID-19 has already taken more than 5.7 million lives worldwide. Moreover, although it is essentially a lung disease, unconventional neurological symptoms have been reported since the beginning of the pandemic, from mild anosmia and ageusia 19,21 , to more severe neurological cases of encephalitis, cerebrovascular disease, ataxia and seizures 37 . Most recently, the description of the "long COVID-19" and the "brain fog", still intrigues physicians and researchers, as cases of cognitive impairment, memory impairment, disorientation and depression have been increasing, evidencing the complexity of the disease 27,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the great majority of people infected with SARS-CoV-2 develop only mild or asymptomatic disease, COVID-19 has already taken more than 5.7 million lives worldwide. Moreover, although it is essentially a lung disease, unconventional neurological symptoms have been reported since the beginning of the pandemic, from mild anosmia and ageusia 19,21 , to more severe neurological cases of encephalitis, cerebrovascular disease, ataxia and seizures 37 . Most recently, the description of the "long COVID-19" and the "brain fog", still intrigues physicians and researchers, as cases of cognitive impairment, memory impairment, disorientation and depression have been increasing, evidencing the complexity of the disease 27,38 .…”
Section: Discussionmentioning
confidence: 99%
“…But, many studies have also confirmed that ACE2 and TMPRSS2 may be expressed at low levels in the brain ( Rothan and Byrareddy, 2020 , Butowt and Bilinska, 2020 ), and the cell types include glial cells, neurons ( Wu et al, 2020 , Guo et al, 2020 ), and epithelial cells from the veins ( Jacob et al, 2020 ). ACE is expressed in the following brain regions: nucleus tractus solitarius, ventral region of the medulla oblongata, substantia nigra (SN), olfactory bulb (OB), ventricle, middle temporal gyrus, cingulate cortex, motor cortex, and other cerebral cortex areas ( Flores, 2021 , Wang et al, 2021 , Faried et al, 2020 ). Therefore, the virus should theoretically be able to infect nerve cells and possibly spread throughout the brain.…”
Section: How Does Sars-cov-2 Affect the Nervous System?mentioning
confidence: 99%
“…At the same time, the Angiotensin Type 1 receptor (AT1 receptor) is over-activated, and the level of angiotensin II increases ( Zou et al, 2020 ). Angiotensin II is a powerful angiotonics in capillary and arteriole vasoconstrictor, affecting blood pressure and cerebral blood flow regulation, and its increass may lead to cerebral hemorrhage and ischemic stroke ( Wang et al, 2021 ). ACE2 expression on endothelial cells is higher in COVID-19 patients with dementia and hypertension, and these patients have generally poorer prognosis ( Buzhdygan et al, 2020a ).…”
Section: How Does Sars-cov-2 Affect the Nervous System?mentioning
confidence: 99%
See 1 more Smart Citation
“…11 The COVID-19 causative virus can cross the blood-brain barrier and invade the brain. 12 The SARS-CoV-2 virus enters the brain either via the olfactory system or the hematogenous route. 13 Endothelial cells on the cerebral vessels contain angiotensin-converting enzyme two receptors which are thought to be a possible viral entry point.…”
Section: Introductionmentioning
confidence: 99%